Cardiovascular adjustments during graded exercise stress - Poderys, J.; Buliuolis, A.; Poderiene, K.; Papieviene, V. (Education. Physical training. Sport, 2012)
Research background and hypothesis. Cardiac function provides an adequate blood supply to all organs thus changes in the performance and functional state of cardiac muscles during exercising are very important. Research aim. The aim of the study was to find out the peculiarities in adjustment of cardiovascular system in dependence on the type of adaptation to physical loads during graded stress. Research methods. The study participants, 17 non-athletes, 23 endurance, 19 sprint and 21 combat sport athletes, underwent a bicycle ergometry of incremental increase in provocative workload (graded stress). A 12-lead ECG was reordered and a computerized program allowed to measure ECG parameter, the ratio of JT/RR intervals and the velocity of adaptation of cardiovascular system to exercising (VAd), by calculating the difference between the relative changes of JT interval and RR interval as a difference: VAd. = (JTi/JT0) 100% - (RRi/RR0) 100%. Research results. No significant functional ischemia was found in endurance cohort during the graded stress while it was expressed in non-athletes` cohort and slightly smaller in sprint and combat cohorts. Maximal values of other ECG or ABP parameters registered during graded stress did not reveal significant differences between cohorts. Discussion and conclusions. Functional ischemia is an important factor limiting muscular and cardiac performance during the graded exercise stress. The exercise type plays a significant role in developing the velocity of adaptation of cardiovascular system at onset of exercising. Faster adaptation at onset of exercise is more characteristic of sprint and combat sports than representatives of endurance or non-athletes.